The Development Dilemma and Path Choice of Innovation and Entrepreneurship Education Based on Game Theory - Huirong Zhu; Qin Wang (Advances in Multimedia)
Innovation and entrepreneurship education (IEE) is a powerful driving force to promote the transformation and development of college education and an effective way to broaden the employment channels. However, IEE has been used to train students in classrooms by college managers who do not systematically think of practical training for innovation and entrepreneurship talents. There are still many difficulties in the process of development of IEE that managers cannot ignore. The relevant models that could deeply analyze the connotation of IEE were established through the game theory that explained the game balance among government, universities, and students in the IEE process. A game theory model explained the external game behavior of universities and students and the internal game behavior between students. Another model analyzed the strategies of players pursuing maximum payoffs from the perspective of both sides of the game and the influences of these strategies on the players. The problems in the process of IEE development are concluded including imperfect management system, unscientific curriculum design, nonideal talent training and unprofessional teachers. Based on it, the development path of IEE is explored through the game concept. A scientific and leading system of management and evaluation is needed to put forward by strengthening the top-level design at the national level, and a win-win game situation between colleges and students will be achieved by the optimized education system.